Association Between Obesity and Clinicopathological Profile of Patients with Newly Diagnosed Non-Metastatic Breast Cancer in Saudi Arabia - Alshamsan B; Suleman K; Agha N; Abdelgawad MI; Alzahrani MJ; Elhassan T; Al-Tweigeri T; Ajarim D; Alsayed A (Dove Medical Press, 2022)
Bader Alshamsan,1,2 Kausar Suleman,1 Naela Agha,1,3 Marwa I Abdelgawad,1,4 Mashari J Alzahrani,1,5 Tusneem Elhassan,1 Taher Al-Tweigeri,1 Dahish Ajarim,1 Adher Alsayed1 1Medical Oncology, Oncology Center, King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia; 2Department of Medicine, College of Medicine, Qassim University, Qassim, Saudi Arabia; 3Northern Ireland Cancer Centre, Belfast City Hospital, Belfast, UK; 4Clinical Oncology Department, Assiut University, Assiut, Egypt; 5Department of Medicine, Medical Oncology, University of Ottawa, Ottawa, ONT, CanadaCorrespondence: Bader Alshamsan, Tel +9660506123866, Email bshmsan@qu.edu.saPurpose: Obesity is prevalent in Saudi Arabia and is associated with adverse clinical features and poor breast cancer (BC) outcomes. We determined the distribution of body mass index (BMI) and evaluated its association with disease characteristics and outcomes in women with non-metastatic BC.Patients and Methods: We conducted a retrospective analysis of a prospectively collected database of consecutive patients treated for non-metastatic BC between 2002 and 2014. Patients were categorized into the following groups: underweight/normal weight (BMI < 25 kg/m2), overweight (BMI 25- 29.9 kg/m2), and obese (BMI ≥ 30 kg/m2). Regression analysis was used to evaluate clinicopathological factors associated with BMI and clinical stage.Results: A total of 2212 patients were enrolled. The median age was 45 years (interquartile range [IQR], 39- 52 years), and the median BMI was 30 kg/m2 (IQR, 26- 34 kg/m2). Most patients were premenopausal (63.6%), nearly half of the patients had stage III disease, and 11.2% were screen-detected. The prevalence of obesity was 53.4%, with a significant difference between the peri/premenopausal (49.4%) and postmenopausal (61.7%) groups (p < 0.001). Obese patients were more likely to be aged > 40 years, be postmenopausal, have a history of oral contraceptive pills, have advanced-stage disease, and have undergone radiation therapy, and were less likely to have human epithelial growth factor 2 (HER2)+ disease than non-obese patients. Premenopausal obese women had fewer hormone receptor-positive and more triple-negative cancers than postmenopausal obese women did. Obesity, non-screening-detected BC, and HER+ status were independent prognostic factors for advanced-stage presentation.Conclusion: The prevalence of obesity and its significant association with advanced BC justify the upscaling of screening services and instituting weight-reduction strategies.Keywords: obesity, body mass index, non-metastatic breast cancer, clinical stage, Saudi Arabia